Biochemical markers of cardiovascular risk in female overweight and obese adolescents - Pajuelo, Jaime (2009)
Introduction: Overweight and obesity are nutritional disorders with features that affect increasingly larger numbers of people with complications risks. Objectives: To determine the presence of cardiovascular risk markers in female overweight and obese adolescents. Design: Descriptive, transversal study. Setting: State Educational Center in Metropolitan Lima. Participants: We studied 149 female adolescents (76 overweight and 73 obese). Interventions: The diagnosis of overweight and obesity followed the World Health Organization’s (WHO) criteria: overweight 85 to 95 percentile and obesity over 95. C-reactive protein (CRP), basal insulin and glucose were determined in serum. Using the latter two we determined HOMA’s index to identify insulin resistance (IR) by Matthew’s equation. PCR diagnostic levels were >3 mg/L, and for high relative risk (HRR) >27 uUI/mL for hyperinsulinaemia and >3,1 for RI. Results: In overweight adolescents we found 2,5% of hyperinsulinaemia, with 7,6% HRR and 20,3% IR; and in obese adolescents 12,3, 24,7 and 27,4% for the same categories; 1,3% of overweight and 8,2% of obese adolescents presented both HRR and IR. Using tertiles HOMA-IR variables are markedly linear with insulin and less intense with weight. Weight, height, BMI and insulin also correlated positively (p <0,001) with HOMA-IR. Conclusions: We found higher risks for obese than for overweight female adolescents. Presence of significant numbers of RI in both groups is worrying as this is a prelude to type 2 diabetes mellitus. Even though PCR prevalence is lower, it calls our attention given the age of those affected. As overweight and obesity have increased, it is reasonable to expect that risks will follow the same direction.